2020
DOI: 10.1111/clr.13679
|View full text |Cite
|
Sign up to set email alerts
|

Fixed full‐arch maxillary prostheses supported by four versus six implants with a titanium CAD/CAM milled framework: 3‐year multicentre RCT

Abstract: ObjectivesThis RCT compares marginal bone level (MBL) change and the clinical parameters after a 3‐year function in maxillary implant‐supported fixed complete dentures (FCDs) treated with four‐implants (4‐I) or six‐implants (6‐I).Material and methodThree centres treated 56 patients with 280 implants allocated to the 4‐I or 6‐I group. Radiographic and clinical examinations were performed. The primary outcome was to investigate MBL change between the groups.ResultsImplant survival rates were 100% and 99% in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 72 publications
(99 reference statements)
2
11
0
Order By: Relevance
“…These results were in accord with the previous studies by Tallarico and colleagues and Toia and colleagues 1,23 and dental prostheses. Toia and colleagues also proposed that convenience of hygienic maintenance, financial exposure, extra bone regeneration procedure (surgical invasiveness), and cost of repairing should be taken into consideration.…”
Section: The Clinical Results Were Comparable Between Two Groupssupporting
confidence: 93%
See 4 more Smart Citations
“…These results were in accord with the previous studies by Tallarico and colleagues and Toia and colleagues 1,23 and dental prostheses. Toia and colleagues also proposed that convenience of hygienic maintenance, financial exposure, extra bone regeneration procedure (surgical invasiveness), and cost of repairing should be taken into consideration.…”
Section: The Clinical Results Were Comparable Between Two Groupssupporting
confidence: 93%
“…These results were in accord with the previous studies by Tallarico and colleagues and Toia and colleagues 1,23 Although the studies showed comparable outcomes between All‐on‐4 and All‐on‐6, Tallarico and colleagues stated that patient demand, compliance, dexterity, financial capability, skeletal maxillomandibular relationship, and residual bone anatomy had to be taken into consideration to customize the proper implant number, position, and dental prostheses. Toia and colleagues also proposed that convenience of hygienic maintenance, financial exposure, extra bone regeneration procedure (surgical invasiveness), and cost of repairing should be taken into consideration.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations